International Financial Statistics Yearbook, 2017. (International Financial Statistics; International Financial Statistics ;, 2017)
This paper focuses on composition of the basket that was changed on the basis of updated data for 1972-1976. The weights of some currencies were also changed. The amount of each of the 16 currencies in the revised basket was such as to ensure that the value of the Special Drawing Right (SDR) in terms of any currency on June 30, 1978 was exactly the same in the revised valuation as in the previous valuation. Since January 1, 1981, the value of the SDR has been determined based on the currencies of the five member countries having the largest exports of goods and services during the 5-year period ending one year before the date of the latest revision to the valuation basket. Broadly reflecting the currencies' relative importance in international trade and finance, the weights are based on the value of the exports of goods and services of the members issuing these currencies and the balances of their currencies officially held by members of the IMF.